Experimental study of state of gastric mucosa in rats under introduction of new derivate of 4-[4-oxo-4h-quinazoline-3-yl] benzoic acid (PC-66) - Kramar, Hanna (ScienceRise: Pharmaceutical Science, 2017)
Screening studies have revealed that the new derivate of 4-[4-oxo-4H-quinazoline-3-yl] benzoic acid (compound PC-66) possess significant antinociceptive and weakly expressed anti-inflammatory and antipyretic activity on different models of pain and inflammation. The cоndition of gastric defense under influence of PC-66 is unknown. The aim of this study was to explore the ability of PC-66 in comparison with diclophenac sodium produce gastric lesions on intact and rats with adjuvant arthritis, and to determine the role of influence on prostaglandin–H-synthase and stable metabolits of nitric oxide in the pathogenesis of these damages. Materials and methods: The impact of PC-66 compound and a diclofenac sodium was explored on macroscopic changes in gastric mucosa under conditions of long-term administration and of experimental inflammation. The spectrophotometric method revealed active prostaglandin-endoperoxide synthase in the rats` GM homogenates against accumulation of oxidized form of adrenaline electron donor. The total content of nitrites and nitrates was determined by reaction with Griess reagent after preliminary restoration of nitrates with a suspension of zinc dust in ammonia solution. Results and Discussion. PC-66 compound, unlike the reference medicine, did not cause significant gastric lesions under conditions of its long-term administration to intact rats. We found that during diclofenac administration, the activity of PGH-synthetase in GM significantly decreased compared to the control, whilst under the influence of PC-66, the activity of this enzyme remained practically unchanged. Administration of PC-66 compound to rats, unlike diclofenac, was associated with a significant increase of stable NO metabolites in GM, whilst this index decreased compared to control under the influence of investigational NSAID. Conclusions: 4- [4-oxo-4H-quinazoline-3-yl] benzoic acid has no damaging effect on the gastric mucosa both in intact animals and in rats with experimental inflammation. The basis of its GM safety rests on lacking inhibitory effect on production of vasodilator molecules in GM of PC-66 compound, unlike diclofenac sodium